Report of the 6th International Workshop on PET in lymphoma. Issue 10 (3rd October 2017) - Nanni, Cristina; Cottereau, Anne Ségolène; Lopci, Egesta; Bodet-Milin, Caroline; Coronado, Monica; Pro, Barbara; Kim, Wong Seog; Trotman, Judith; Barrington, Sally; Duhrsen, Ulrich; Vander Borght, Thierry; Zamagni, Elena; et al.
Abstract: Two hundred and ten nuclear medicine physicians, radiologists, and hematologists from 26 countries attended the 6th International Workshop on Positron Emission Tomography (PET) in Lymphoma and Myeloma held in Menton, France, in September 2016. The meeting was under the auspices of the European Lymphoma Institute (ELI), the European Association of Nuclear Medicine (EANM) the Lymphoma Study Association (LYSA), the Italian Foundation on Lymphoma (FIL) and the Carnot Institute for Lymphoma (CALYM). Forty scientific posters were presented. For the first time, specialists in the field of multiple myeloma (MM) were involved in the expert session. The aim was to establish from the experience of Italian and French studies new guidelines of FDG-PET/CT reporting for myeloma staging and restaging. The meeting dedicated an entire session to MM imaging followed by a session on the role of PET in Peripheral T cell Lymphoma. An entire session addressed the issues of Deauville scale particularly for end treatment assessment and the challenging consequences of immunomodulatory treatments on PET reporting. A specific session presented the potential role of baseline metabolic tumor measurement to predict outcome and identify different risk categories and the main results obtained in different lymphoma entities were described. Whether it could replace clinical staging has been extensively discussed. The more recent results obtained in the H10 trial have been presented and compared to the published data in early stage Hodgkin lymphoma. Finally, the ongoing studies using PET for guiding therapeutic strategies have been reported by the various lymphoma cooperative groups that participated to the meeting.